Positive electrode layer

By using a secondary particle structure containing tungsten in the positive active substance of a lithium-ion secondary battery and optimizing the valence of tungsten through XAFS analysis, the problem of increasing primary resistance of lithium-ion secondary batteries in the prior art is solved, and better battery performance is achieved.

JP2025058668AActive Publication Date: 2025-04-09TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023168744
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The existing lithium-ion secondary battery using tungsten as the positive electrode active substance has an increase in resistance during the first charge and discharge, and it is difficult to effectively suppress it.

Method used

The positive electrode active material with a secondary particle structure containing sodium, potassium, lithium, nickel and tungsten is used, and the inside and surface of the tungsten is contained. The XAFS analysis ensures that the tungsten's valence is between 4 and 6 valences, and the battery performance is optimized by adjusting the content and position of tungsten.

Benefits of technology

It effectively suppresses the increase in the primary resistance of the lithium-ion secondary battery and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058668000001_ABST
    Figure 2025058668000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode capable of suppressing the initial resistance of a battery.SOLUTION: A positive electrode layer contains a positive electrode active material 10 and carbon nanotubes 11. The positive electrode active material contains a lithium-nickel-based complex oxide and tungsten that presents at least in the interior or on a surface of the lithium-nickel-based complex oxide, and the positive electrode active material is secondary particles 2 including a plurality of primary particles 1 and voids formed between the plurality of primary particles. The positive electrode layer contains, as the carbon nanotubes, first carbon nanotubes of which at least some are included in the voids of the secondary particles, and spectrums at rising positions (10,195 eV-10,206 eV) of peaks of L absorption edges of tungsten measured by X-ray absorption fine structure analysis (XAFS) satisfy formula (1): (a-b) / (c-b)≤0.79.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode layer for use in a lithium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries are increasingly being put to practical use not only as small power sources for mobile phones and notebook computers, but also as medium- and large-sized power sources for automobiles and power storage.

[0003] Research has been conducted focusing on positive electrode active materials to improve the performance of lithium ion secondary batteries. For example, Patent Document 1 discloses a nonaqueous electrolyte secondary battery having a positive electrode containing, as a positive electrode active material, porous particles of a lithium composite oxide having a specific porosity and containing two or more specific voids, the porous particles having a coating containing tungsten oxide (WO3, hexavalent tungsten) and lithium tungstate on the surface thereof, for the purpose of providing a nonaqueous electrolyte secondary battery having low initial resistance and suppressed resistance increase during repeated charging and discharging.

[0004] Moreover, Patent Document 2 discloses a positive electrode for a lithium ion secondary battery that uses a positive electrode active material containing tungsten, which has a valence of 4. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-018895 [Patent Document 2] JP 2023-082743 A Summary of the Invention [Problem to be solved by the invention]

[0006] In a battery using a positive electrode active material containing tungsten, it is expected that the initial resistance of the battery can be suppressed. However, there is room for further improvement in suppressing the initial resistance.

[0007] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a positive electrode capable of suppressing the initial resistance of a battery. [Means for solving the problem]

[0008] [1] A positive electrode layer for use in a lithium ion secondary battery, The positive electrode layer contains a positive electrode active material and carbon nanotubes, The positive electrode active material contains a lithium nickel-based composite oxide containing at least Li, Ni, O, and an X element (excluding Li and Ni) having a valence of 1 or 2, and tungsten present in at least one of the interior and the surface of the lithium nickel-based composite oxide, the positive electrode active material is a secondary particle having a plurality of primary particles and voids formed between the plurality of primary particles, The positive electrode layer contains, as the carbon nanotubes, first carbon nanotubes at least partially contained in the voids of the secondary particles, and The spectrum of the tungsten L absorption edge peak rise position (10195 eV to 10206 eV) measured by X-ray absorption fine structure analysis (XAFS) is Formula (1): (ab) / (cb)≦0.79 [In formula (1), a represents the energy (eV) at which the spectral slope is greatest in the range of 10195 eV to 10206 eV, When the spectral intensity at a (eV) is A, b represents the energy (eV) at which the spectral intensity of WO2 (tungsten (IV) oxide) becomes A in the range of 10195 eV to 10206 eV, and c represents the energy (eV) at which the spectral intensity of WO3 (tungsten (VI) oxide) becomes A in the range of 10195 eV to 10206 eV.].

[0009] [2] The positive electrode layer according to [1], wherein the lithium nickel-based composite oxide contains, as the X element, at least one of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba.

[0010] [3] The positive electrode layer according to [1] or [2], wherein in the lithium nickel-based composite oxide, a molar ratio of the X element to the Ni element is 0.05 or more and 0.13 or less.

[0011] [4] The positive electrode layer according to any one of [1] to [3], wherein in the lithium nickel-based composite oxide, the average valence of the Ni element is 2.90 or more and 3.50 or less.

[0012] [5] The positive electrode layer according to any one of [1] to [4], wherein the lithium nickel-based composite oxide contains at least Be as the X element. Effect of the Invention

[0013] The present disclosure has an effect of providing a positive electrode capable of suppressing an increase in battery resistance. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating a positive electrode active material according to the present disclosure. [Diagram 2] FIG. 2 is a diagram for explaining formula (1) in the present disclosure. [Diagram 3] FIG. 2 is a diagram for explaining formula (1) in the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The positive electrode layer in the present disclosure will be described in detail below. In this specification, the term "to" indicating a range of values ​​is used to mean that the values ​​before and after the range include the lower limit and upper limit.

[0016] 1. Positive electrode layer The positive electrode layer in the present disclosure is a positive electrode layer used in a lithium ion secondary battery, and contains a positive electrode active material and carbon nanotubes. The positive electrode active material contains a lithium nickel-based composite oxide containing at least Li, Ni, O, and an X element (excluding Li and Ni) having a valence of 1 or 2, and tungsten present at least in the interior and on the surface of the lithium nickel-based composite oxide. The positive electrode active material is a secondary particle having a plurality of primary particles and a void formed between the plurality of primary particles. The positive electrode layer contains, as the carbon nanotube, a first carbon nanotube at least a part of which is included in the void of the secondary particle. The positive electrode layer satisfies formula (1): (ab) / (cb)≦0.79 when measured by X-ray absorption fine structure analysis (XAFS). In this specification, the "void formed between the primary particles" may be referred to as the "void of the secondary particle". Moreover, the "voids of secondary particles" usually refer to the internal space of a secondary particle surrounded by a plurality of primary particles.

[0017] According to the present disclosure, the positive electrode active material contains a lithium nickel-based composite oxide containing a specified X element, and tungsten, and therefore the positive electrode layer containing the positive electrode active material can suppress the initial resistance of the battery.

[0018] Lithium nickel-based composite oxides, such as NCM-based and NCA-based, are known to be used as positive electrode active materials. 2+ ) is a lithium-ion (Li +), there is a risk of cation mixing occurring between the lithium ions and nickel ions. If cation mixing occurs, the movement of lithium ions during charging and discharging of the battery may be hindered, and the battery resistance may increase.

[0019] In addition, a positive electrode active material containing tungsten is known. Here, as will be described in detail later, when the above formula (1) is satisfied, the valence of tungsten contained in the positive electrode active material is tetravalent or has an average valence between tetravalent and hexavalent, so that the battery resistance such as the initial resistance can be suppressed.

[0020] In this regard, the present inventors have found that there is a risk that cation mixing may be promoted in a positive electrode active material containing tungsten and a lithium nickel-based composite oxide, and that there is room for further improvement in suppressing battery resistance. This is because there is a risk that the oxidation of Ni may be insufficient due to tungsten. In contrast, in the positive electrode active material of the present disclosure, the lithium nickel-based composite oxide contains an X element having a valence of 1 or 2, so that the valence of Ni can be increased (Ni can be sufficiently oxidized). As a result, it is possible to suppress cation mixing and suppress an increase in battery resistance. In addition, LiNi 0.9 X 0.1 In the lithium nickel-based composite oxide represented by O2, when the valence of X is 4, the valence (average valence) of Ni is 2.89, but when the valence of X is 3, the valence of Ni is 3.00.

[0021] (1) Positive electrode active material The positive electrode active material in the present disclosure contains a lithium nickel-based composite oxide that contains at least Li, Ni, O, and an X element (excluding Li and Ni) whose valence is 1 or 2. The X element is a so-called typical element that does not have a valence other than 1 or 2.

[0022] The lithium nickel-based composite oxide may contain, as the X element, only an element whose valence is 1, or only an element whose valence is 2, or may contain both an element whose valence is 1 and an element whose valence is 2. It is preferable that the lithium nickel-based composite oxide contains, as the X element, at least an element whose valence is 2.

[0023] Examples of the X element include alkali metal elements and alkaline earth metal elements. Examples of the X element include Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba. The lithium nickel composite oxide may contain one or more of the above elements as the X element.

[0024] In the lithium nickel-based composite oxide, the molar ratio of the X element to the Ni element is, for example, 0.05 or more, may be 0.06 or more, or may be 0.07 or more, while the molar ratio of the X element to the Ni element is, for example, 0.13 or less, may be 0.12 or less, or may be 0.10 or less.

[0025] In the lithium nickel-based composite oxide, the molar ratio of X element to Li element is, for example, 0.01 or more, and may be 0.03 or more, while the molar ratio of X element to Li element is, for example, 0.1 or less, and may be 0.07 or less, or may be 0.05 or less.

[0026] The lithium nickel-based composite oxide may further contain transition metal elements such as Mn, Co, and Al. In this case, the molar ratio of Ni element to all transition metal elements in the lithium nickel-based composite oxide is preferably 0.5 or more. The molar ratio of Ni element to all transition metal elements may be 0.6 or more, or may be 0.7 or more. On the other hand, the molar ratio of Ni element to all transition metal elements is, for example, 0.9 or less.

[0027] In the lithium nickel composite oxide, the average valence of the Ni element is preferably high. The average valence of the Ni element is, for example, 2.90 or more, may be 2.95 or more, or may be 3.00 or more. On the other hand, the average valence of the Ni element is, for example, 3.50 or less, may be 3.30 or less, or may be 3.10 or less.

[0028] The composition of the lithium nickel composite oxide is, for example, Li[Ni a Me b X (1-a-b) In the above formula, a satisfies 0.5≦a<1.0, and b satisfies 0≦b<0.5. Me is at least one element selected from Mn, Co, and Al, and X is the X element described above.

[0029] The lithium nickel-based composite oxide constitutes primary particles in the positive electrode active material, which will be described later.

[0030] The positive electrode active material in the present disclosure also contains tungsten.

[0031] The tungsten contained in the positive electrode active material may be tetravalent tungsten, or may be a mixture of tetravalent tungsten and hexavalent tungsten in which the spectrum including the rising position (10195 eV to 10206 eV) of the peak at the L absorption edge of tungsten satisfies formula (1) described later.

[0032] Examples of tetravalent tungsten compounds include WO2, lithium tungstate containing tetravalent tungsten, and lithium nickel cobalt manganese-based composite oxides containing tetravalent tungsten.

[0033] Examples of the hexavalent tungsten compound include lithium tungstate containing hexavalent tungsten, such as WO3 and Li2WO4, and lithium nickel cobalt manganese-based composite oxides containing hexavalent tungsten.

[0034] The tungsten content (the tungsten content in the entire positive electrode active material) is not particularly limited, but may be, for example, 0.1 mass% or more, 0.3 mass% or more, or 0.5 mass% or more. On the other hand, the tungsten content may be, for example, 1.0 mass% or less, 0.8 mass% or less, or 0.6 mass% or less. If the tungsten content is within the above range, the battery resistance of the lithium ion secondary battery can be further reduced. The tungsten content can be determined by elemental analysis using ICP (inductively coupled plasma) emission spectrometry.

[0035] Moreover, the tungsten is present in at least one of the inside and the surface of the lithium nickel composite oxide. Tungsten may be present in the inside of the lithium nickel composite oxide in the positive electrode active material. For example, tungsten may be present as a component constituting the lithium nickel composite oxide, or may be present dispersedly in the inside of the lithium nickel composite oxide. In this way, tungsten may constitute the primary particles of the positive electrode active material together with the lithium nickel composite oxide. Moreover, tungsten may be present on the surface of the lithium nickel composite oxide in the positive electrode active material. That is, tungsten may be present so as to cover the surface of the primary particles (primary particles of the lithium nickel composite oxide) in the positive electrode active material, or may be present so as to cover the surface of the secondary particles (secondary particles of the lithium nickel composite oxide). Moreover, tungsten may be present both inside and on the surface of the lithium nickel composite oxide.

[0036] Moreover, the positive electrode active material in the present disclosure is a secondary particle having a plurality of primary particles and voids formed between the plurality of primary particles.

[0037] The primary particles may have voids. In other words, the primary particles may be porous particles. The voids are the same as those in the secondary particles described below.

[0038] Average particle size of primary particles (D50 ) is, for example, 0.01 μm or more and 100 μm or less. 50 ) refers to the cumulative 50% particle size in the volume-based particle size distribution measured with a laser diffraction particle size analyzer.

[0039] The secondary particles have voids. The ratio of voids (porosity) is not particularly limited, but is, for example, 20% or more and 50% or less. The porosity can be determined, for example, by observing the cross section of the positive electrode active material with a scanning electron microscope (SEM). The porosity can also be determined by measuring the pore distribution using a mercury porosimeter.

[0040] The voids may have a predetermined average pore size (radius), for example, 1 nm or more and 500 nm or less. The average pore size can be determined, for example, by mercury porosimeter measurement.

[0041] Average particle size of secondary particles (D 50 ) is, for example, 0.1 μm or more and 1000 μm or less. 50 ) is the same as above.

[0042] The proportion of the positive electrode active material in the positive electrode layer is not particularly limited, but is, for example, 50 mass % or more and 90 mass % or less.

[0043] The method for producing the positive electrode active material in the present disclosure is not particularly limited as long as it can produce the above-mentioned positive electrode active material, and examples of the method include the methods described in the examples below.

[0044] (2) Carbon nanotubes (CNTs) The positive electrode layer in the present disclosure contains carbon nanotubes, which function as a conductive material.

[0045] The positive electrode layer contains, as carbon nanotubes, first carbon nanotubes at least a part of which is included in the voids of secondary particles. Here, the location of the carbon nanotubes will be described with reference to FIG. 1. FIG. 1 is a schematic cross-sectional view illustrating a positive electrode active material in the present disclosure. As shown in FIG. 1(a), in a positive electrode active material 10, the first carbon nanotubes 11 may be entirely included in the voids α (inside) of secondary particles 2 formed by aggregation of primary particles 1. On the other hand, as shown in FIG. 1(b), the first carbon nanotubes 11 may be partially present in the voids α (inside) of secondary particles 2, and partially present outside (on the outer surface) of the secondary particles.

[0046] As a method for incorporating the first carbon nanotubes into the voids of the secondary particles, for example, the methods described in the Examples below can be mentioned.

[0047] The positive electrode layer may contain, as the carbon nanotubes, second carbon nanotubes that are not enclosed in the voids of the secondary particles.

[0048] The second carbon nanotubes can be contained in the positive electrode layer by adding the carbon nanotubes during the preparation of the positive electrode mixture in the examples described below.

[0049] The ratio of the first carbon nanotube to the second carbon nanotube in the positive electrode layer is not particularly limited. When the mass of the first carbon nanotube is X1 and the mass of the second carbon nanotube is X2, X1 / X2 is, for example, 0.1 or more and 3 or less.

[0050] The proportion of carbon nanotubes in the positive electrode layer is not particularly limited, but is, for example, 0.5 mass % or more and 20 mass % or less.

[0051] (3) Positive electrode layer The positive electrode layer in the present disclosure has a spectrum at the rising position (10195 eV to 10206 eV) of the peak at the L absorption edge of tungsten measured by X-ray absorption fine structure analysis (XAFS): Formula (1): (ab) / (cb)≦0.79 [In formula (1), a represents the energy (eV) at which the spectral slope is greatest in the range of 10195 eV to 10206 eV, When the spectral intensity at a (eV) is A, b represents the energy (eV) at which the spectral intensity of WO2 (tungsten (IV) oxide) becomes A in the range of 10195 eV to 10206 eV, and c represents the energy (eV) at which the spectral intensity becomes A in the range of 10195 eV to 10206 eV of WO3 (tungsten (VI) oxide).

[0052] Here, the above formula (1) will be described with reference to Fig. 2 and Fig. 3. Fig. 2 is a diagram showing XAFS measurement spectra of the positive electrode layer (positive electrode sample), WO2 and WO3 in the present disclosure. Specifically, Fig. 2 shows spectra including the rising position (10195 eV to 10206 eV) of the peak of the L absorption edge of tungsten by XAFS measurement of the positive electrode sample, WO2 (tungsten oxide (IV)) and WO3 (tungsten oxide (VI)). Fig. 3 is a diagram showing a partial enlargement of the rising position of the peak of the L absorption edge of tungsten in the XAFS measurement spectrum of the positive electrode sample, WO2 and WO3.

[0053] The rising position of the peak of the L absorption edge of tungsten in the XAFS measurement spectrum represents the valence of the element tungsten. In the present disclosure, the energy (eV) at which the slope of the spectrum is maximum at the rising position (10195 eV to 10206 eV) of the peak of the L absorption edge of tungsten in the XAFS measurement spectrum of the positive electrode sample is a, and is used as an index of the rising position of the peak. a can be specified as the energy of the peak top of the derivative obtained by differentiating the spectrum in the range of 10195 eV to 10206 eV. When the spectrum intensity at a (eV) is A, the energy (eV) at which the spectrum intensity becomes A in the range of 10195 eV to 10206 eV of WO2 (tungsten oxide (IV)) is b, and the energy (eV) at which the spectrum intensity becomes A in the range of 10195 eV to 10206 eV of WO3 (tungsten oxide (VI)) is c. Here, WO2 is used as a standard sample of tetravalent tungsten, and WO3 is used as a standard sample of hexavalent tungsten.

[0054] In formula (1), when (ab) / (cb)=1, the tungsten in the positive electrode layer (positive electrode active material) is interpreted as hexavalent. In formula (1), when (ab) / (cb)=0, the tungsten in the positive electrode layer is interpreted as tetravalent. In formula (1), when (ab) / (cb)≦0.79 is satisfied, the tungsten in the positive electrode layer is interpreted as tetravalent or has an average valence between tetravalent and hexavalent.

[0055] Tungsten having an average valence between 4 and 6 is considered to be a mixture of 4-valent tungsten and 6-valent tungsten, and has a lower average valence than 6-valent tungsten, and has high conductivity and the effect of lowering activation energy. Therefore, when the tungsten in the positive electrode layer is 4-valent or has an average valence between 4 and 6, it is considered that the tungsten exerts high conductivity and the effect of lowering activation energy, thereby reducing the cell resistance. In addition, low-valence tungsten is easily dissolved in Ni, Co, Mn, etc. used in the positive electrode active material, and when it is dissolved, it is considered that the diffusion resistance of lithium ions can be reduced by expanding the crystal axis of the crystal structure of the positive electrode active material.

[0056] In formula (1), (ab) / (cb) may be 0.70 or less, 0.60 or less, or 0.50 or less. On the other hand, in formula (1), (ab) / (cb) may be, for example, 0.20 or more, 0.30 or more, or 0.40 or more. The XAFS measurement for determining (ab) / (cb) in formula (1) will be described in the Examples below.

[0057] The positive electrode layer in the present disclosure may contain at least one of an electrolyte and a binder in addition to the above-mentioned positive electrode active material and carbon nanotubes. The positive electrode layer may also contain a conductive material other than the above-mentioned carbon nanotubes.

[0058] The electrolyte may be a liquid electrolyte or a solid electrolyte. Examples of the liquid electrolyte include an electrolyte containing an organic solvent such as ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and a supporting salt such as LiPF6. Examples of the solid electrolyte include inorganic solid electrolytes such as oxide solid electrolytes and sulfide solid electrolytes. Examples of the binder include rubber-based binders and fluoride-based binders. Examples of the conductive material other than carbon nanotubes include particulate carbon materials such as acetylene black (AB) and Ketjen black (KB), and fibrous carbon materials such as carbon nanofibers (CNF).

[0059] The thickness of the positive electrode layer is not particularly limited, but is, for example, not less than 0.1 μm and not more than 1000 μm.

[0060] The method for producing the positive electrode layer is not particularly limited, but may be, for example, a method in which a positive electrode mixture containing at least the above-mentioned positive electrode active material (positive electrode active material in which the first carbon nanotube is enclosed in the voids of the secondary particles) is applied to a substrate such as a positive electrode current collector and dried. At least one of carbon nanotubes (second carbon tubes), a binder, a conductive material, and an electrolyte may be added to the positive electrode mixture.

[0061] 2. Lithium-ion secondary battery The positive electrode layer in the present disclosure is used in a lithium ion secondary battery. Therefore, the present disclosure can also provide a lithium ion secondary battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the positive electrode layer being the above-mentioned positive electrode layer. In addition, the lithium ion secondary battery usually includes a positive electrode current collector that collects current from the positive electrode layer, and a negative electrode current collector that collects current from the negative electrode layer. The lithium ion secondary battery may be a liquid battery containing a liquid electrolyte as the electrolyte, or may be a solid battery containing a solid electrolyte as the electrolyte.

[0062] The positive electrode layer is as described in "1. Positive electrode layer." The negative electrode layer, electrolyte layer, positive electrode current collector, and negative electrode current collector may be conventionally known members used in lithium ion secondary batteries.

[0063] Examples of applications of lithium ion secondary batteries include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the battery as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0064] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0065] [Example 1] (Preparation of Positive Electrode Active Material) A positive electrode active material containing a lithium nickel-based composite oxide and tungsten was prepared as follows.

[0066] First, a raw material aqueous solution (concentration 30 wt%) was prepared by dissolving a Ni element source (nickel sulfate), a Co element source (cobalt sulfate), a Mn element source (manganese sulfate) and an X element source (beryllium sulfate) in ion-exchanged water. Meanwhile, a reaction solution in which the pH was adjusted using sulfuric acid and ammonia water was prepared in a reaction vessel. In addition, a sodium hydroxide aqueous solution was prepared as a pH adjusting solution. Next, the raw material aqueous solution was added to the reaction solution at a predetermined rate under stirring, and neutralized with the pH adjusting solution. The crystallized product was washed with water, filtered and dried to obtain composite hydroxide particles (precursor particles). The drying was performed at 120°C for 16 hours.

[0067] The obtained precursor particles were mixed with lithium carbonate. The molar ratio of lithium to the total of nickel, cobalt, manganese, and beryllium was 1.1. This mixture was fired at 870°C for 15 hours in an electric furnace. After cooling to room temperature in the furnace, it was crushed to obtain a lithium nickel composite oxide (Li(Ni 0.8 Co 0.1 Mn 0.05 Be 0.05 )O2) was obtained. When the obtained lithium nickel composite oxide was observed under a microscope, it was confirmed that there were sufficient gaps between the primary particles (voids in the secondary particles).

[0068] The obtained lithium nickel composite oxide was mixed with tungsten (IV) oxide (WO2) and tungsten (VI) oxide (WO3) at a ratio of 0.5 mass% for the tungsten ratio (W / (lithium nickel composite oxide + WO2 + WO3)). The mixture was treated in a mechanochemical device at 3000 rpm for 30 minutes and further heat-treated at 150°C for 1 hour to obtain a positive electrode active material as a lithium nickel composite oxide coated with tungsten oxide (WO2, WO3).

[0069] The obtained positive electrode active material was also analyzed by transmission electron microscope-energy dispersive X-ray analysis (TEM-EDX). The results showed that tungsten was incorporated into the primary particles of the lithium metal composite oxide. In other words, tungsten was present both inside and on the surface of the lithium nickel composite oxide in the obtained positive electrode active material.

[0070] (Preparation of positive electrode layer) The obtained positive electrode active material, conductive material (carbon nanotube), and binder (polyvinylidene fluoride) were weighed in a mass ratio of positive electrode active material:conductive material:binder=88:10:2, and mixed to obtain a positive electrode composite. The positive electrode composite and 1 mass% of zirconia balls (diameter 3.0 mm) relative to the positive electrode composite were put into a kneading device (manufactured by Thinky Corporation) and mixed for 10 minutes. The obtained positive electrode composite was applied onto a positive electrode current collector (Al foil) using a film applicator (with film thickness adjustment function, All Good Co., Ltd.), and then dried at 80°C for 5 minutes. As a result, a positive electrode structure having a positive electrode current collector and a positive electrode layer was obtained.

[0071] (Production of evaluation battery (lithium ion secondary battery)) A paste for forming a negative electrode active material layer was prepared by mixing natural graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a mass ratio of C:SBR:CMC=98:1:1 in ion-exchanged water. This paste was applied to both sides of a negative electrode current collector (Cu foil) with a thickness of 10 μm, dried, and then pressed to produce a negative electrode structure having a negative electrode layer on both sides of the negative electrode current collector.

[0072] In addition, two 24 μm-thick porous polyolefin sheets having a three-layer structure of PP / PE / PP were prepared as separator sheets. The prepared positive electrode structure and negative electrode structure were stacked with the two prepared separator sheets and wound to prepare a wound electrode body. Electrode terminals were attached to the positive and negative electrodes of the prepared wound electrode body by welding, and the resultant was housed in a battery case having a liquid injection port.

[0073] [Examples 2 and 3] Except for preparing the positive electrode active material using magnesium sulfate or calcium sulfate as the X element source, a battery for evaluation was fabricated in the same manner as in Example 1. The ratios and valences of Ni element, Co element, Mn element and X element in the lithium nickel-based composite oxide are as shown in Table 1.

[0074] [Comparative Example] Except for preparing the positive electrode active material without using the X element source, the evaluation battery was produced in the same manner as in Example 1. The ratios and valences of Ni element, Co element and Mn element in the lithium nickel-based composite oxide are as shown in Table 1.

[0075] [evaluation] (SEM observation) A cross-polisher was used to cut the positive electrode layers obtained in the examples and comparative examples. The cross-sections obtained were observed using a FE-SEM (field emission scanning electron microscope) to confirm the positions of the carbon nanotubes in the positive electrode layer. The results are shown in Table 2. As shown in Table 2, in all of the examples and comparative examples, the carbon nanotubes were present both on the surface and inside of the active material. In other words, the positive electrode layers in the examples and comparative examples contained both the first carbon nanotube and the second carbon nanotube.

[0076] (XAFS measurement of the positive electrode layer) The positive electrodes obtained in the examples and comparative examples were subjected to XAFS measurement using the following device. In addition, the standard samples of tungsten oxide (IV) (WO2) and tungsten oxide (VI) (WO3) were also subjected to XAFS measurement using the following device. The value of (ab) / (cb) in the above formula (1) was calculated from the spectrum at the rising position (10195 eV to 10206 eV) of the peak at the L absorption edge of tungsten measured by XAFS. The results are shown in Table 2. Equipment: Hard X-ray XAFS at Aichi Synchrotron Light Center, Science and Technology Foundation Measurement range: 9897-11297 eV (peak position of the L absorption edge of tungsten) Measurement method: The positive electrode was measured by the fluorescence method, and the tungsten compound was measured by the transmission method. The transmission method for measuring the tungsten compound standard material detects the transmitted X-rays when irradiated with incident X-rays, while the fluorescence method for measuring the positive electrode detects the fluorescent X-rays generated when irradiated with incident X-rays, so even though the measurement methods are different, they can be expressed as the same spectrum. By normalizing the XAFS measurement data using the analysis software Athena, it is possible to compare the tungsten in the tungsten compound standard material with the tungsten in the positive electrode. In order to ensure the reproducibility of formula (1), a standard sample was measured every time a positive electrode sample was measured, and minute deviations were corrected.

[0077] (Initial resistance evaluation) The evaluation batteries prepared in the examples and comparative examples were subjected to activation treatment as described below, and then the initial resistance was measured. The evaluation batteries were placed in an environment of 25°C. Activation (initial charging) was performed using a constant current-constant voltage method, and each evaluation battery was charged at a constant current of 1 / 3C to 4.2V, and then charged at a constant voltage until the current value reached 1 / 50C, and fully charged. Thereafter, each evaluation battery was discharged at a constant current of 1 / 3C to 3.0V. In this manner, activation treatment was performed on each evaluation battery.

[0078] Each evaluation battery that had been subjected to the activation treatment was adjusted to an open circuit voltage of 3.70V. This was placed in a temperature environment of -28°C. Discharged at a current value of 20C for 8 seconds to obtain a voltage drop amount ΔV. Next, the voltage drop amount ΔV was divided by the discharge current value (20C) to calculate the battery resistance, which was taken as the initial resistance. The initial resistance of the comparative example was taken as 100%, and the initial resistance of each example was evaluated relatively. The results are shown in Table 2.

[0079] (Evaluation of Ni mixing ratio) The positive electrode layers prepared in the examples and comparative examples were subjected to metal content evaluation by ICP-MS and crystal structure evaluation by XRD. Using the results, Rietveld analysis was performed to calculate the Ni mixing ratio. The results are shown in Table 2.

[0080] [Table 1]

[0081] [Table 2]

[0082] As shown in Table 2, the Ni mixing rate was smaller in all of the Examples than in the Comparative Examples, and the initial resistance was suppressed. This indicates that the positive electrode layer in the present disclosure can suppress the resistance of the battery. Also, as shown in Table 2, in the Examples and Comparative Examples, (ab) / (cd) was 0.79 or less, indicating that the tungsten in the positive electrode layer was tetravalent or had an average valence between tetravalent and hexavalent. [Explanation of symbols]

[0083] 1...Primary particle 2…Secondary particles 10...Cathode active material 11...First carbon nanotube

Claims

1. A positive electrode layer for use in a lithium ion secondary battery, The positive electrode layer contains a positive electrode active material and carbon nanotubes, The positive electrode active material contains a lithium nickel-based composite oxide containing at least a Li element, a Ni element, an O element, and an X element (excluding Li and Ni) having a valence of 1 or 2, and tungsten present in at least one of the inside and the surface of the lithium nickel-based composite oxide, the positive electrode active material is a secondary particle having a plurality of primary particles and voids formed between the plurality of primary particles, The positive electrode layer contains, as the carbon nanotubes, first carbon nanotubes at least partially contained in the voids of the secondary particles, and The spectrum of the tungsten L absorption edge peak rise position (10195 eV to 10206 eV) measured by X-ray absorption fine structure analysis (XAFS) is Formula (1): (a-b) / (c-b)≦0.79 [In formula (1), a represents the energy (eV) at which the spectral slope is greatest in the range of 10195 eV to 10206 eV, When the spectral intensity at a (eV) is A, b is WO 2 represents the energy (eV) at which the spectral intensity of (tungsten(IV) oxide) becomes A in the range of 10195 eV to 10206 eV, c is WO 3 (tungsten(VI) oxide) represents the energy (eV) at which the spectral intensity becomes A in the range of 10195 eV to 10206 eV.)

2. 2. The positive electrode layer according to claim 1, wherein the lithium nickel-based composite oxide contains, as the X element, at least one of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba.

3. 2. The positive electrode layer according to claim 1, wherein in the lithium nickel-based composite oxide, a molar ratio of the X element to the Ni element is 0.05 or more and 0.13 or less.

4. 2. The positive electrode layer according to claim 1, wherein in the lithium nickel-based composite oxide, the average valence of the Ni element is 2.90 or more and 3.50 or less.

5. The positive electrode layer according to claim 1 , wherein the lithium nickel-based composite oxide contains at least Be as the X element.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery

    JP2012064573A

  • Conductive agent for lithium ion secondary battery positive electrode and lithium ion secondary battery using the same

    JP2012221672A

  • Cathode active material, secondary battery cathode, secondary battery and cathode active material production method

    JP2015195130A

  • Method for manufacturing positive electrode of lithium ion secondary battery, and method for manufacturing lithium ion secondary battery

    JP2022178476A

  • Positive electrode for lithium-ion secondary battery

    JP2023082743A